2006
DOI: 10.1080/00480169.2006.36692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial and extended exposure to an endophyte-infected tall fescue seed diet on faecal and urinary excretion of ergovaline and lysergic acid in mature geldings

Abstract: Exposure time to the ergot alkaloids had a limited effect on the route of elimination or the amounts of ergovaline or lysergic acid excreted by horses. The primary alkaloid excreted was lysergic acid, and urine was the major route of elimination. These data will aid future research to improve animals' tolerance to toxic endophyte-infected tall fescue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 25 publications
1
33
1
Order By: Relevance
“…1978); detection and quantification of ergot alkaloids in urine, bile, milk, and tissues (Westendorf et al, 1993;Stuedemann et al, 1998;Durix et al, 1999;Realini et al. 2005;Schultz et al, 2006); and in vitro transport studies Shappell and Smith, 2005).…”
Section: Absorptionmentioning
confidence: 95%
“…1978); detection and quantification of ergot alkaloids in urine, bile, milk, and tissues (Westendorf et al, 1993;Stuedemann et al, 1998;Durix et al, 1999;Realini et al. 2005;Schultz et al, 2006); and in vitro transport studies Shappell and Smith, 2005).…”
Section: Absorptionmentioning
confidence: 95%
“…Our metabolomics approach was optimized for extraction of the entire metabolome, not specifically EA, and this is one potential reason for the lack of plasma ergovaline (Klotz and Nicol, 2016;Schultz et al, 2006) or urine lysergic acid (Lodge-Ivey et al, 2006;Schultz et al, 2006) identification. Rapid ergovaline metabolism and distribution to liver and kidney tissues also impedes its identification in the plasma (Ayers et al, 2009;De Lorme et al, 2007;Zbib et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…A series of in vivo alkaloid-balance studies all came to similar conclusions regarding the conversion of ergovaline to lysergic acid in geldings (Schultz et al 2006), wethers (De Lorme et al 2007) and steers (Merrill et al 2007). Specifically, these studies all reported intake concentrations of ergovaline and lysergic acid and concentrations of these compounds in the urine and faeces.…”
Section: Bioavailabilitymentioning
confidence: 71%
“…In all three studies, there was less ergovaline and more lysergic acid excreted than consumed. Reported recoveries of ergovaline were 58.3%, 35.4% and 55% for Schultz et al (2006), De Lorme et al (2007 and Merrill et al (2007) respectively, whereas recoveries for lysergic acid in all three studies were >200% of intake. All ergovaline recovered was in the faeces, as Stuedemann et al (1998) reported that excretion of ergovaline occurs via the biliary system, whereas the majority of lysergic acid was recovered in urine.…”
Section: Bioavailabilitymentioning
confidence: 99%